Pengaruh Lingkungan Sekolah Terhadap Perilaku Beragama Siswa di MAN 1 Tulungagung Tahun Pelajaran 2020/2021 - Indah Kusuma Dewi (Sustainable, 2021)
In addressing the moral degradation and today’s development, it is necessary for efforts in developing on the religious behavior of the students as a fortress in their daily life. This research was conducted in order to know how the influence of school toward religious behavior in MAN 1 Tulungagung in 2020/2021 academic year. This research is descriptive correlative research which describes the influence of school to the religious behavior of students in MAN 1 Tulungagung. Samples taken randomly by using Slovin formula as the results are 151 students. The instrument used in this research was a questionnaire and documentation. Data were analyzed using simple regression analysis. The research reveals that; The school environment contributes to religious behavior in MAN of Tulungagung district by 49.1%, This result suggests that to improve the quality of students' religious behavior can be done by instilling religious learning in the school environment.